2017
DOI: 10.5005/jp-journals-10024-2116
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Caries: A Review

Abstract: Aim: To review and update the current knowledge about early childhood caries (ECC) and its etiology, prevalence, risk factors, management, and preventive strategies. Background:Early childhood caries is a disease affecting significantly both well-developed and industrial nations. The ECC can significantly affect the child's quality of life, as it may lead to infection, swelling, pain, and other symptoms. The ECC affects children after eruption of primary teeth until age of around 5 years. Review results:The EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 39 publications
0
58
0
9
Order By: Relevance
“…National and international oral health policy should emphasize oral health promotion and prevention for children. It is important to prevent and control ECC, as the consequence of untreated ECC negatively affects chewing ability, speech development, and the formation of a positive self‐image . ECC is a preventable disease, and plenty of preventive methods exist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…National and international oral health policy should emphasize oral health promotion and prevention for children. It is important to prevent and control ECC, as the consequence of untreated ECC negatively affects chewing ability, speech development, and the formation of a positive self‐image . ECC is a preventable disease, and plenty of preventive methods exist.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that adopted random sampling method, had a favorable sample size (N > 100), established comparability between respondents and non-respondents and good response rate (>80%), used wellestablished diagnosis criteria, had good reliability between examiners (kappa value >0.6), and adopted appropriate statistic methods were rated as a full score or 8 (Appendix S1). The methodological quality of the studies was categorized as poor (0-2), moderate (3)(4)(5), and good (6)(7)(8), according to the modified NOS for descriptive purposes. Preferred Reporting Items for Systematic Reviews and Meta-Analyses was used as a basis for reporting in this systematic review.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Children who grew up plagued with dental caries and who have family members with serious dental caries are more likely to be at risk of having dental caries in the future. Some of the reasons identified that have led to this state are: limited to no access to dental care, lack of accessible preventive measures such as water fluoridation, supplementation of fluoride, and pit and fissure sealants, and the lack of information on the importance of oral well-being (Alazmah, 2017). Patterns of dental disease reflect distinct risk profiles across countries that are related to living conditions, lifestyles and environmental factors, and the implementation of preventive oral health schemes is needed (Petersen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%